Effect of instability resistance training on sports performance among athlets : a systematic review - Gao, Jianxin; Abdullah, Borhannudin; Omar Dev, Roxana Dev; Guo, Qi; Lin, Xiaofei (Servei de Publicacions i Intercanvi Cientific , Universitat de les Illes Balears, 2023)
The aim of this investigation is to systematically review the impact of instability resistance training (IRT) on sports performance, providing both theoretical and practical insights for athletes in routine training. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, databases such as Web of Science, EBSCOhost (SPORTDiscus), PubMed, and Scopus were employed for the comprehensive collection of original references. A total of 402 articles were gathered, with only 17 meeting the specified analytical criteria. The quality of each article was assessed using the PEDro scale, resulting in scores ranging from 2 to 6 across the 17 articles. IRT exhibited significant efficacy in enhancing sports and athletic performance across disciplines such as Judo, cricket, weightlifting, rifle shooting, sprinting, handball, soccer, and basketball, with the exception of 25 male elite golf players. Theoretically, this study posits that IRT, rooted in functional training, represents an advancement in activating core muscles, fostering coordination between agonistic and antagonistic muscles, and enhancing muscle proprioception “ pivotal physiological foundations for augmenting exercise performance. Moreover, by emphasizing the integration of training actions and the role of the "power chain," IRT, adopting an unstable format akin to specialized exercises or increasing difficulty, aims to enhance training efficiency. Empirical evidence demonstrates that continuous IRT positively influences sports performance, with moderate IRT identified as a secure and effective stimulation method. Consequently, this review advocates for the incorporation of IRT into athletes' daily training routines to optimize sports performance.